Optimalisasi Pengadaan Buku di Perpustakaan: Sistem Pendukung Keputusan Berbasis MOORA - Fani Zanemi; M. Faisal Afiff Tarigan (Jurnal Garuda Pengabdian Kepada Masyarakat, 2024)
Book procurement is a stage carried out by libraries to increase reading interest in book collections. Care must be taken when purchasing books so that the books used in the library collection can be utilized effectively by visitors. Different evaluation models established by each library are applied to select library books for use in their collections. The subject of this test is the FST Library of North Sumatra State Islamic University. The selection of books in the Library of the Faculty of Science & Technology, North Sumatra State Islamic University is actually carried out by library staff. This assessment uses the MOORA method to determine the recommended position of library books. The stages are alternative input, criteria and weights, then forming a matrix, then normalizing the matrix, normalizing the weight matrix, then looking for the benefit criteria by adding and subtracting the normalized results and then getting the final result of the preference value. Where the information used in this management is seven selected pieces of information obtained from the estimation results. The first ranking is A5, namely for e- commerce books with an index value of 0.149 and the last ranking is A1 for management information systems books with an index value of -0.092.